Titanium and silicon dioxide-coated fabrics for management and tuning of infrared radiation - CANOĞLU, SUAT; YÜKSELOĞLU, SEVHAN MÜGE (My University, 2022)
Far infrared radiation (FIR) is emitted by every body at a given temperature, including the human body. FIR ranging between 4-14 mu m is considered useful for cell growth, and the human body emits a maximum of infrared (IR) radiation at the wavelength of approximately 9.3 mu m. In the present study, fabrics based on five different raw textiles having the same yarn count as well as the same weaving patterns were designed and created. Some of them were subjected to a coating process. The fabrics to be tested were as follows: coated with TiO2 nanoparticles, coated with SiO2 nanoparticles, coated fabric that does not contain bioceramic nanoparticle (BNFC), and non-coated fabrics (NCF). The structural characterization of the resulting samples was performed using scanning electron microscopy (SEM), abrasion tests, and air permeability. Following the structural characterization, the infrared emissivity properties were investigated using infrared thermography as well as attenuated total reflectance Fourier-transform infrared spectroscopy in the 8-14 IR range. According to the experimental findings, the fabrics coated with TiO2 and SiO2 displayed increased infrared emissivity values compared to the uncoated ones. In addition, it was observed that the use of bioceramic powders had no effect on air permeability and abrasion properties.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Kimya; Analitik Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Chemistry; Analytical Chemistry; Natural Sciences; Engineering and Technology; KİMYA, ANALİTİK; Temel Bilimler (SCI); MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ALETLER & GÖSTERİM; CHEMISTRY, ANALYTICAL; CHEMISTRY; Natural Sciences (SCI); ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING; Engineering, Computing & Technology (ENG); INSTRUMENTS & INSTRUMENTATION; Genel Mühendislik; Filtrasyon ve Ayırma; Kimya (çeşitli); Mühendislik (çeşitli); Elektrik ve Elektronik Mühendisliği; Enstrümantasyon; Genel Kimya; Fizik Bilimleri; General Engineering; Filtration and Separation; Chemistry (miscellaneous); Engineering (miscellaneous); Electrical and Electronic Engineering; Instrumentation; General Chemistry; Physical Sciences; smart textiles; infrared emissivity; infrared manipulation; infrared thermography; FTIR; STAINLESS-STEEL TEXTILES; EMISSION; IMPROVE; smart textiles; infrared emissivity; infrared manipulation; infrared thermography; FTIR